Sustainability Synergies or Silos? The Opportunity Costs of Local Government Organizational Capabilities. - Deslatte, Aaron; Stokan, Eric (Public Administration Review)
Public managers serve many sovereigns, work within fiscal constraints, and face competing demands for finite resources. This article applies a strategic management lens to local government sustainability capabilities to examine the conditions under which local governments diversify into new areas of service delivery and when they do not. Building on recent efforts to apply resource‐based theories to the public sector, the authors distinguish between more and less fungible capabilities and posit that local government officials make such commitments to enhance the competitiveness of their communities. Two surveys of U.S. cities provide evidence that governments that rely on tax incentive‐based development approaches may struggle to make sustainable development gains. Such cities are more likely to devote resources disproportionately to delivering benefits to firms at the risk of incurring increasing opportunity costs over time. Prior commitments to traditional, firm‐based economic development capabilities appear to inhibit their ability to pursue broader sustainability policies. However, economic development strategic planning can also positively influence some investments in greenhouse gas reduction efforts. Moreover, cities facing more competition for development are more likely to integrate planning and performance measurement to assess their sustainability commitments.